Political opposition: an analytical study of its conditions and functions - Hafez Alwan Hamadi Al-Dlemi (The Scientific Journal of Cihan University– Sulaimaniya, 2018)
Political Manifestation An analytical study of its functions and working conditions. The subject of political vulnerability occupies an important place among those who study political systems and those who are keen on democracy, not to mention those political groups aspiring to power. The political opposition has risen to the point where it has become one of the political and constitutional institutions of the state. Some have argued that it is one of the means by which it maintains the social peace, the effectiveness and stability of the regime, and, oddly enough, by referring to former US president Abraham Lincoln: The voice of the opposition is outstripped by the sound of bullets. «Some even took the political opposition to sanctification and prestige. In Britain, it is» the opposition of Her Majesty the Queen « However, there is ignorance or ignorance of the importance of political opposition because it addresses the intractable problem faced by the political systems in the third world, which is to prevent or reduce the role and most important not to absorb in the performance of its function in favor of strengthening the political system, prompting the political forces opposed to resort to means that may not fit the system Claims democracy ... in accordance with the rule that «there is no real democracy without political opposition The political opposition represents one of the democratic leaders and an indicator of the improvement of the political system and the effectiveness of its three constitutional institutions, and to face mistakes and correct them. More importantly, the alternative was put forward and our research included four questions. And the second is the political opposition systems, the second is the political opposition in the constitutional systems, the third is the political opposition, and the fourth and final subject is the terms of the political opposition The most important conclusion is that the political opposition is an essential element that can not be ignored or overlooked, especially in the political systems that seek to achieve democracy. We have reached ten conclusions, the most important of which is that the political opposition and its various objectives and objectives, one of which is conducive to achieving security and social peace.